Geopolitical Risks and Movements in Islamic Bond and Equity Markets: A Note. Issue 3 (16th April 2019) - Bouri, Elie; Demirer, Riza; Gupta, Rangan; Marfatia, Hardik A.
Abstract: This study applies a non-parametric causality-in-quantiles test to examine the causal effect of geopolitical risks on return and volatility dynamics of Islamic equity and bond markets. Geopolitical risks are generally found to impact Islamic equity market volatility measures, rather than returns. However, geopolitical risks tend to predict both returns and volatility measures of Islamic bonds. Interestingly, causality, when it exists for returns and/or volatility of Islamic equities and bonds, is found to hold over entire conditional distributions of returns and volatilities, barring the extreme ends of the same.